Salvia tilantongensis (Lamiaceae), a new species of the Mixteca Alta, Oaxaca, Mexico - González-Gallegos, Jesús Guadalupe; Aguilar-Santelises, Remedios (Instituto de Ecología, A.C., 2014)
Salvia tilantongensis is described and illustrated as a new species from the Mixteca Alta of Oaxaca, Mexico. The new taxon is morphologically similar to Salvia fulgens and S. gesneriiflora. It differs from both by its exfoliating bark, petioles attached to a thickened base from the node, narrower leaves, smaller floral bracts and with a shorter apex, longer pedicels during fructification, acute and long aristate lobes of the calyx, middle lobe of lower corolla lip incurved-concave, shorter filament and style, and longer lower stigmatic branch. Furthermore, it is distinguished from S. fulgens by the absence of a pair of papillae inside the basal portion of the tube of the corolla. Detailed descriptions of S. fulgens and S. gesneriiflora are also provided.